Advances in DNA Vaccines - Simmerman, James Mark (The Nurse practitioner, 2002)
Extraordinary advances in biotechnology make DNA vaccines the most promising area of vaccinology. This article reviews the public health impact of vaccines in the 20th century, summarizes immunologic concepts, and updates the status of DNA vaccine development and its impact on clinical practice.